Spatial Politics: Questioning Land Use in the IKN Region from a Spatial Production Perspective - Hastira, Muh Fichriyadi; Arsyad, Armin; Kambo, Gustiana; Muhammad, Muhammad; Saad, Muhammad; Arifin, Mimi (Universitas Muhammadiyah Tangerang, 2025)
The relocation of Indonesia’s national capital to East Kalimantan reflects spatial-political dynamics in which state, corporate, and community interests collide. This study employs a qualitative case study combining field observations, document analysis, and in-depth interviews with the IKN Authority, East Kalimantan provincial officials, Dayak and Balik traditional leaders, NGOs such as AMAN, and civil society actors. Findings show that spatial planning is dominated by the central government and investors, while local participation remains limited. Key policy instruments, including the IKN Law and Detailed Spatial Plan (RDTR), tend to override indigenous rights, marginalize traditional living spaces, and prioritize long-term land concessions for corporations. Such exclusionary practices have intensified land conflicts, forced evictions, and ecological damage in the Sepaku and Samboja areas, including deforestation, biodiversity loss, and water resource degradation. The results indicate that IKN development is not a neutral technical exercise but a contested political project. This aligns with Lefebvre’s conception of space as a contested social product shaped by power. The study contributes to debates on spatial politics in Indonesia while underscoring the need for inclusive, just, and ecologically sustainable planning.Peralihan Ibu Kota Negara Indonesia ke Kalimantan Timur mencerminkan dinamika spasial-politik di mana kepentingan negara, korporasi, dan masyarakat saling bertabrakan. Studi ini menggunakan metode studi kasus kualitatif yang menggabungkan pengamatan lapangan, analisis dokumen, dan wawancara mendalam dengan Otoritas IKN, pejabat provinsi Kalimantan Timur, pemimpin tradisional Dayak dan Balik, LSM seperti AMAN, dan aktor masyarakat sipil. Temuan menunjukkan bahwa perencanaan ruang didominasi oleh pemerintah pusat dan investor, sementara partisipasi lokal tetap terbatas. Instrumen kebijakan utama, termasuk Undang-Undang IKN dan Rencana Tata Ruang Terperinci (RDTR), cenderung mengabaikan hak-hak masyarakat adat, menggeser ruang hidup tradisional, dan memprioritaskan konsesi tanah jangka panjang bagi korporasi. Praktik-praktik eksklusif ini telah memperparah konflik tanah, pengusiran paksa, dan kerusakan ekologi di wilayah Sepaku dan Samboja, termasuk deforestasi, kehilangan keanekaragaman hayati, dan degradasi sumber daya air. Hasil penelitian menunjukkan bahwa pengembangan IKN bukanlah praktik pembangunan yang bersifat netral, melainkan proyek politik yang kontroversial. Hal ini sejalan dengan konsepsi Lefebvre tentang ruang sebagai produk sosial yang diperebutkan dan dibentuk oleh kekuasaan. Studi ini berkontribusi pada debat tentang politik ruang di Indonesia sambil menekankan perlunya perencanaan yang inklusif, adil, dan berkelanjutan secara ekologi.